2014
DOI: 10.1177/8755122514551419
|View full text |Cite
|
Sign up to set email alerts
|

Propofol-Associated Priapism in a Pediatric Patient

Abstract: Objective: To report a case of priapism in an adolescent male following the use of propofol for sedation. Case Report: A 13-year-old male with developmental delay was admitted to intensive care secondary to pneumonia and persistent paroxysmal choreoathetosis. In attempt to stop the choreoathetosis and progressive rhabdomyolysis, he was sedated with 50 mg of intravenous propofol, which successfully resolved the choreoathetosis. Within minutes after the injection, he developed priapism, and within 1 hour it reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The priapism resolved within an hour after aggressive intravenous hydration. 7 Compared with the previously reported case reports, the treatment of our patient’s priapism event was the quickest and least invasive that was accomplished by prompt recognition of the priapism event and discontinuation of propofol, which led to our patient’s erection subsiding within minutes. Also, we monitored our patient very closely for recurrence of the priapism because the longer the priapism persists the higher likelihood that surgery would be necessary for treatment as was seen in the previously mentioned case reports.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The priapism resolved within an hour after aggressive intravenous hydration. 7 Compared with the previously reported case reports, the treatment of our patient’s priapism event was the quickest and least invasive that was accomplished by prompt recognition of the priapism event and discontinuation of propofol, which led to our patient’s erection subsiding within minutes. Also, we monitored our patient very closely for recurrence of the priapism because the longer the priapism persists the higher likelihood that surgery would be necessary for treatment as was seen in the previously mentioned case reports.…”
Section: Discussionmentioning
confidence: 67%
“…Doherty et al reported that each patient in previous cases of propofol-associated priapism was also on concomitant opioid medication. 7 Similarly, our patient was on a continuous fentanyl infusion. Opioid medications are thought to potentially decrease peripheral vascular resistance, leading to the potentiation of propofol’s effects on inducing priapism.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Within minutes of receiving a propofol injection for choreoathetosis a 13-year-old male developed priapism. No further propofol was administered, the patient received aggressive intravenous hydration and the priapism resolved after approximately 1 hour without further intervention (Doherty & Khandhar, 2015). In Corten et al (2017) case report, the authors can only speculate about the factors responsible for their 48-year-old Caucasian male's prolonged erection lasting approximately 1 day.…”
Section: Discussionmentioning
confidence: 99%